2018
DOI: 10.2147/idr.s167616
|View full text |Cite
|
Sign up to set email alerts
|

Optimal infusion rate in antimicrobial therapy: explosion of evidence in the last five years

Abstract: BackgroundSporadic studies in antimicrobial therapy have evaluated the effects of infusion rates on therapeutic and economic outcomes, and new findings may challenge the regular infusion regimen.MethodsFocusing on studies comparing the outcomes of different infusion regimens, the relevant literature was identified by searching PubMed, Web of Science, and Scopus from January 1, 2013 to March 1, 2018. Papers were finally chosen using a PRISMA flowchart.ResultsAntimicrobials with the superiority of prolonged infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
(60 reference statements)
0
15
0
1
Order By: Relevance
“…In contrast with vancomycin, the dosage of beta-lactam administered does not seem to be an aggravating risk factor, as shown by Moenster et al [37], who found that patients treated with high-dose PT (≥18 g/day) had similar incidence of AKI than those treated with standard dosing. The effect of infusion strategy has also been assessed, as the use of extended infusions has been adopted in some critical care settings due to its association with improved outcomes and safety in severe infections [43]. Beta-lactam infusion strategy does not seem to alter the risk of nephrotoxic AKI with beta-lactams [44] and specifically with PT therapy in combination with vancomycin.…”
Section: Risk Factors For Vpt-associated Akimentioning
confidence: 99%
“…In contrast with vancomycin, the dosage of beta-lactam administered does not seem to be an aggravating risk factor, as shown by Moenster et al [37], who found that patients treated with high-dose PT (≥18 g/day) had similar incidence of AKI than those treated with standard dosing. The effect of infusion strategy has also been assessed, as the use of extended infusions has been adopted in some critical care settings due to its association with improved outcomes and safety in severe infections [43]. Beta-lactam infusion strategy does not seem to alter the risk of nephrotoxic AKI with beta-lactams [44] and specifically with PT therapy in combination with vancomycin.…”
Section: Risk Factors For Vpt-associated Akimentioning
confidence: 99%
“…And there are many potential pathogens that can cause sepsis [10]. More importantly, there is no drug or treatment that can effectively cure sepsis [11]. Therefore, it is necessary for us to develop new therapeutic methods for ALI treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The exact combined number of variables that causes sepsis is complex (9). There are many potential pathogens that could cause sepsis, and more importantly, there is no special medicine or therapeutic approach that effectively cures sepsis (10).…”
mentioning
confidence: 99%